Culinary MSME Sustainability: Financing, Trust, Networks, and Adaptation - Rani Rani; Suhardi Suhardi; Mat Amin (MARGIN ECO, 2026)
This study aims to examine the effect of access to financing, consumer trust, and business networks on the sustainability of culinary MSMEs in Bangka Belitung, with adaptation strategy as a mediating variable in the post-pandemic era. This topic is important as culinary MSMEs face sustainability challenges due to changing consumer behavior, limited resources, and dynamic market conditions. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with 189 respondents. The results indicate that consumer trust and business networks significantly influence adaptation strategy, while access to financing shows a weaker effect. Furthermore, adaptation strategy emerges as the most dominant factor influencing business sustainability and serves as a partial mediator between the independent variables and sustainability. These findings highlight that MSME sustainability is not solely determined by resource availability, but by the ability to strategically adapt to changing business environments.